2017
DOI: 10.1159/000480237
|View full text |Cite
|
Sign up to set email alerts
|

Is Omentectomy Necessary for Non-Endometrioid Endometrial Cancer

Abstract: Background: In subtypes of non-endometrioid endometrium cancers (non-ECC), it is not clear whether the omentectomy is a part of debulking if visual assessment is normal. Recently, the ESMO-ESGO-ESTRO Endometrial Consensus Conference Working Group in their report titled “Endometrial Cancer: diagnosis, treatment and follow-up” recommended that omentectomy be performed in the serous subtype, but not in carcinosarcoma, undifferentiated endometrial carcinoma or clear cell. In this study, the question is whether ome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 21 publications
1
21
0
Order By: Relevance
“…In our series, 11 patients were upstaged from stage I to stage IV after omentectomy. Our multivariate analysis showed that adnexal invasion was a risk factor for omental involvement, which is consistent with the results obtained in Kaban’s study [14]. Thus, adnexal involvement might predict the need for omentectomy.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…In our series, 11 patients were upstaged from stage I to stage IV after omentectomy. Our multivariate analysis showed that adnexal invasion was a risk factor for omental involvement, which is consistent with the results obtained in Kaban’s study [14]. Thus, adnexal involvement might predict the need for omentectomy.…”
Section: Discussionsupporting
confidence: 92%
“…The prevalence of omental metastasis in USC ranged from 10 to 17.4% [[12], [13], [14]]. Even in women with noninvasive serous carcinoma limited to the endometrium, the occurrence of omental metastases was as high as 5.1–9.8% (58/591) in clinical stage I nonendometrioid type endometrial cancer [15,16].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[10] The National Comprehensive Cancer Network (NCCN) guideline supports that all of the non-endometrioid types are at high risk and that the omentectomy is part of the staging surgery. [11] Kaban et al 's [12] study showed that all patients with non-endometrioid type omentectomy were proposed, which seems reasonable that omentectomy is part of the staging surgery in non-endometrioid histologies.…”
Section: Discussionmentioning
confidence: 99%
“…In a randomised controlled trial comparing modified radical (Piver-Rutledge class II) hysterectomy to the standard extrafascial (Piver-Rutledge class I) or simple total hysterectomy in stage I endometrial carcinoma, Signorelli et al showed no differences in locoregional control and survival [172]. The high risk of microscopic omental metastases in stage I serous and undifferentiated endome-trial carcinoma and in carcinosarcoma suggests that omentectomy should be part of staging surgery in these patients [173]. The low rate of omental metastases in apparent clinical stage I endometrioid and clear cell carcinoma does not justify the procedure [174].…”
Section: Standard Surgical Proceduresmentioning
confidence: 99%